Sind mittelständische Betriebe der Jobmotor der deutschen Wirtschaft? - Joachim Wagner; Lena Koller; Claus Schnabel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
In public discussion in Germany it is often argued that jobs are mainly created in small and medium-sized firms (i.e. the Mittelstand), whereas large firms tend to reduce their number of jobs. An empirical analysis for the period 1999 to 2005 with data of all western and eastern German firms that have at least one employee covered by social insurance shows that the job engine Mittelstand hypothesis is too undifferenciated. While small and medium-sized firms contribute more than proportionally to job growth, they are also heavily involved in job losses. In contrast, large firms with 250 employees and more record shares of job growth and destruction which are lower than their share in employment. This implies that economic policy measures which focus on certain size classes of firms cannot be justified by superior employment growth in these size classes.
Keywords: J23; L60; L80; 330; Klein- und Mittelunternehmen; Verarbeitendes Gewerbe; Dienstleistungssektor; Betriebsgröße; Beschäftigungseffekt; Vergleich; Deutschland